DESIGN AND CONSTRUCTION OF COCONUT GRATERING MACHINE WITH 220 VOLT ELECTRIC MOTOR - Pratama, Indra Yoga; Arifin, Zaenal (PROFISIENSI : Jurnal Program Studi Teknik Industri, 2023)
The coconut shredding process has relatively large energy and special abilities so that the results are good and the hands are not injured. To facilitate traction and maintain hygiene and increase the capacity of shredding in households and small industries, many coconut grate machines have been designed or made with various models and prices vary. One of the designs or designs circulating in the market is a grate engine that uses a motor engine with gasoline fuel. This machine is designed in such a way as to increase safety for users, speed up the coconut shredding process, increase capacity, and maintain hygiene from shredded coconuts. But household-scale and small-scale coconut shredded machine tools are still relatively expensive. In this design, a tool was made with a mini coconut grate machine redesign to reduce material costs and manufacturing costs. Make changes to the shape and dimensions for the frame and supports. In addition, changes to engine components with a household-scale electric motor with a power of 220 volts